2019
DOI: 10.1001/jamapediatrics.2018.4954
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence of Hospitalization for Vaccine-Preventable Infections in Children Following Solid Organ Transplant and Associated Morbidity, Mortality, and Costs

Abstract: IMPORTANCE Pediatric transplant recipients are at risk for vaccine-preventable infections owing to immunosuppression, suboptimal response to vaccines before and after transplant, and potential underimmunization if transplant occurred early in life. However, the incidence and burden of illness from vaccine-preventable infections in this population is unknown. OBJECTIVES To evaluate in pediatric solid organ transplant recipients the number of hospitalizations for vaccine-preventable infections in the first 5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 65 publications
1
67
1
Order By: Relevance
“…As we stressed in our article, the complex ethical issues provide valuable lessons for the present and the future. 1 We question several of the authors' comments. They state that our article maintained that separation of twins to be adopted was "characteristic of the era's thinking."…”
Section: Comment and Responsementioning
confidence: 98%
See 2 more Smart Citations
“…As we stressed in our article, the complex ethical issues provide valuable lessons for the present and the future. 1 We question several of the authors' comments. They state that our article maintained that separation of twins to be adopted was "characteristic of the era's thinking."…”
Section: Comment and Responsementioning
confidence: 98%
“…Prevalence of e-cigarette use among US adolescents substantially increased from 2017 to 2018. 1 Whether prevalence also increased among young adults (18-24 years)-a population with high vaping rates 2 and vulnerability to nicotine dependence and other health consequences of nicotine exposure 3 -is unknown.…”
Section: Prevalence Of E-cigarette Use Among Adults In the United Stamentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we reported recurrent and terminal events simultaneously. Each recurrent event in patients increases the risk of additional recurrent and terminal events (25). For example, the mortality rate is higher after the fourth hospitalization compared to that after the first hospitalization (6).…”
Section: ' Discussionmentioning
confidence: 99%
“…Influenza is another important infection in patients posttransplantation. In a study of pediatric liver transplant recipients, influenza was the most common vaccine preventable disease that causes hospitalization [12]. Data suggest that influenza vaccine has decreased immunogenicity in posttransplant recipients compared to healthy controls [13,14].…”
Section: Influenzamentioning
confidence: 99%